Energy Consumption Saving in Embedded Microprocessors Using Hardware Accelerators - Gian Carlo Cardarilli; Luca Di Nunzio; Rocco Fazzolari; Marco Re; Francesca Silvestri; Sergio Spanò (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
This paper deals with the reduction of power consumption in embedded microprocessors. Computing power and energy efficiency are becoming the main challenges for embedded system applications. This is, in particular, the caseof wearable systems. When the power supply is provided by batteries, an important requirement for these systems is the long service life. This work investigates a method for the reduction of microprocessor energy consumption, based on the use of hardware accelerators. Their use allows to reduce the execution time and to decrease the clock frequency, so reducing the power consumption. In order to provide experimental results, authors analyze a case of study in the field of wearable devices for the processing of ECG signals. The experimental results show that the use of hardware accelerator significantly reduces the power consumption.